Physician attitudes toward health information exchange: results of a statewide survey - Wright, Adam (BMJ Group, 2010)
OBJECTIVE: To assess physicians' attitudes toward health information exchange (HIE) and physicians' willingness to pay to participate in HIE. DESIGN: We conducted a cross-sectional mail survey of 1296 licensed physicians (77% response rate) in Massachusetts in 2007. MEASUREMENTS: Perceptions of the potential effects of HIE on healthcare costs, quality of care, clinicians' time, patients' privacy concerns, and willingness to pay for HIE. RESULTS: After excluding 253 physicians who did not see any outpatients, we analyzed 1043 responses. Overall, 70% indicated that HIE would reduce costs, while 86% said it would improve quality and 76% believed that it would save time. On the other hand, 16% reported being very concerned about HIE's effect on privacy, while 55.0% were somewhat concerned and 29% not at all concerned. Slightly more than half of the physicians (54%) said they would be willing to pay an unspecified monthly fee to participate in HIE, but only 37% said they would be willing to pay $150 per month for it. Primary care physicians and those in larger practices tended to have more positive attitudes toward HIE. CONCLUSIONS: Physicians perceive that HIE will have generally positive effects, though a considerable fraction harbor concerns about privacy. While physicians may be willing to participate in HIE, they are not consistently willing to pay to participate. HIE business models that require substantial physician subscription fees may face significant challenges.